Mimosa diplotricha (Fabaceae) Recruits Native Pollinators, But Does it Matter? - I.N. Egbon; O.P. Nzie; J. Rotimi (Journal of Applied Sciences and Environmental Management, 2020)
Here an invasive alien weed Mimosa diplotricha, which attracts native pollinators to its flowers, was studied to establish the composition, diversity and the pattern of visitation of native flower-visiting species found on the weed as it expands its range unabatedly in Nigeria. From five randomly selected quadrats of 2 m x 2 m, repeated fourteen times, the floral visitors of M. diplotricha were sampled. Using diversity indices, non-parametric species estimators, Whittaker and Bray Curtis similarity indices, the composition and diversity of floral visiting bees and allied insects were reported. Thirteen insect taxa were encountered from a total of 1548 individuals in three Orders, albeit of low diversity in which the majority of floral visitors (or pollinators) were hymenopterans: the main being Chalicodoma species, followed by Xylocopa species, X. senior, and Apis mellifera. Non-parametric estimators revealed a high sampling efficiency of the true species visiting mimosa between sunrise and noon. That the floral resources of M. diplotricha supported high abundance of few species and some species with low abundance indicate that those of the latter case were casual visitors. In sum, that the population of M. diplotricha is still  expanding in Nigeria against the backdrop of their utilisation by native pollinators is suggestive of a continual recruitment of the pollinators, which may prefer the novel host within a mosaic of widely scattered native flowering plants. Further investigations of pollinators’ choices may be apt to understand the true impact of invasive alien flowering weeds on native pollinators and crop productivity.